2014
DOI: 10.1111/exd.12476
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of heat shock protein 90 inhibition on humoral immune responses

Abstract: Heat shock protein 90 (Hsp90) inhibition blocks T-cell-linked inflammatory disease pathways and exhibits therapeutic activity in autoimmune disease mouse models, including the blistering disease epidermolysis bullosa acquisita. Although we previously showed that preformed autoreactive plasma cells do not seem to be directly affected by anti-Hsp90 treatment, immunomodulatory effects of Hsp90 inhibition on (auto-)antibody responses are not yet fully understood. In this study, the Hsp90 blocker 17-DMAG inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…These future investigations could yield some relevant information about the role of Hsp90 in MMP and, together with already existing knowledge on the powerful anti-inflammatory and anti-scarring effects of anti-Hsp90 treatment [14][15][16][17][18][19][20][21]25,[28][29][30], possibly support the introduction of nontoxic Hsp90 inhibitors for future medical management of patients with this potentially devastating disease that may otherwise cause permanent damage when therapy is delayed or ineffective.…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 85%
See 2 more Smart Citations
“…These future investigations could yield some relevant information about the role of Hsp90 in MMP and, together with already existing knowledge on the powerful anti-inflammatory and anti-scarring effects of anti-Hsp90 treatment [14][15][16][17][18][19][20][21]25,[28][29][30], possibly support the introduction of nontoxic Hsp90 inhibitors for future medical management of patients with this potentially devastating disease that may otherwise cause permanent damage when therapy is delayed or ineffective.…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 85%
“…Based on the above, we hypothesize that pharmacological Hsp90 blockade could represent a double-edged sword in the treatment of MMP by pleiotropic targeting of the mentioned Hsp90 inhibitor-prone pathophysiological factors involved in both inflammatory subepidermal blister formation and cicatricial processes [19][20][21]25,[28][29][30]. Due to their additional anti-cancer activity, Hsp90 inhibitors could even be proclaimed as a triple-edged sword against the malignancy-associated anti-laminin 332 subtype of MMP [12].…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for analysis of novel therapeutic agents intended to target granulocyte-dependent inflammatory pathways involved in autoimmune tissue damage, as it reproduces the efferent autoimmune response independently of T cells, B cells, and plasma cells (6). While we previously showed that pharmacological Hsp90 inhibition directly affects autoreactive T cells and B cells, but not plasma cells (1,2), the results of our current study extend these observations revealing that this treatment is also capable of directly inhibiting the effector phase of granulocyte-driven autoantibody-induced skin blistering.…”
Section: Discussionmentioning
confidence: 99%
“…A novel strategy to inhibit autoreactive T cell responses is derived from experiments using inhibitors of the cell stressinducible chaperone heat shock protein 90 (Hsp90) in experimental EBA (Kasperkiewicz et al, 2011). Currently tested in clinical trials for therapy of cancer patients due to its inhibitory effects on malignant cells (Solárová et al, 2015), anti-Hsp90 treatment is also increasingly becoming a research focus in autoimmune diseases, including blistering disorders, as it exerts potent immunomodulatory actions (Collins et al, 2013;de Zoeten et al, 2011;Kasperkiewicz et al, 2011;Tukaj et al, 2014aTukaj et al, , 2014bTukaj et al, , 2014cTukaj et al, , 2015aTukaj et al, , 2015b. Application of Hsp90 inhibitors before and after disease onset blocked EBA development and induced clinical recovery associated with suppressed autoantibody production compared with vehicletreated animals in immunization-induced EBA, respectively.…”
Section: Gm-csf and Neutrophilsmentioning
confidence: 99%